2015
DOI: 10.1089/scd.2014.0381
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2 and Its Related Ligands Play a Novel Role in Supporting the Pluripotency and Proliferation of Human Pluripotent Stem Cells

Abstract: Basic fibroblast growth factor (bFGF) is a crucial factor sustaining human pluripotent stem cells (hPSCs). We designed this study to search the substitutive factors other than bFGF for the maintenance of hPSCs by using human placentaderived conditioned medium without exogenous bFGF (hPCCM -), containing chemokine (C-X-C motif) receptor 2 (CXCR2) ligands, including interleukin (IL)-8 and growth-related oncogene a (GROa), which were developed on the basis of our previous studies. First, we confirmed that IL-8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…4 D). Importantly, in line with the prostemness functions of ELR + chemokines (Liu et al, 2011; Jung et al, 2015), treatment with the CXCR-2 inhibitor also reduced the level of CD44 + CD24 low/− TICs within the breast carcinoma cells co-cultured with MTD-CAFs (Fig. 4 E).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…4 D). Importantly, in line with the prostemness functions of ELR + chemokines (Liu et al, 2011; Jung et al, 2015), treatment with the CXCR-2 inhibitor also reduced the level of CD44 + CD24 low/− TICs within the breast carcinoma cells co-cultured with MTD-CAFs (Fig. 4 E).…”
Section: Resultssupporting
confidence: 58%
“…Tumors with elevated levels of ELR + chemokines are more aggressive, and this phenotype has been attributed to their ability to stimulate angiogenesis or promote macrophage-induced immune suppression within tumors (Ali and Lazennec, 2007; Seifert et al, 2016). In addition, ELR + chemokines can also foster the growth and survival of stem cells (Liu et al, 2011; Jung et al, 2015). Consistently, both an in vitro angiogenesis assay and a tumor neovascularization assay revealed that the MTD-CAFs markedly promoted endothelial tube formation and tumor neovascularization, which could be efficiently blocked by SB225002, a specific inhibitor of the conserved ELR + chemokine receptor CXCR-2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma GROa levels correlate inversely with severity of disease in an experimental murine model of myocarditis 43 . Both GROa and CXCR2 were recently implicated in human pluripotent stem cell pluripotency and proliferation 39 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CXCR2 hindered hPSC self-renewal and resulted in a gradual increase in cell differentiation 350. The CXCL8-CXCR1/2 signaling regulates maintenance and cellular growth of glioblastoma stem cells.…”
Section: The Cxcl8-cxcr1/2 Axis In Cancermentioning
confidence: 99%